Cyclic Voltammetry and Impedance Spectroscopy Behavior Studies of Polyterthiophene Modified Electrode - Naima Maouche; Belkacem Nessark (International Journal of Electrochemistry)
We present in this work a study of the electrochemical behaviour of terthiophene and its corresponding polymer, which is obtained electrochemically as a film by cyclic voltammetry (CV) on platinum electrode. The analysis focuses essentially on the effect of two solvents acetonitrile and dichloromethane on the electrochemical behaviour of the obtained polymer. The electrochemical behavior of this material was investigated by cyclic voltammetry and electrochemical impedance spectroscopy (EIS). The voltammograms show that the film of polyterthiophene can oxide and reduce in two solutions; in acetonitrile, the oxidation current intensity is more important than in dichloromethane. The impedance plots show the semicircle which is characteristic of charge-transfer resistance at the electrode/polymer interface at high frequency and the diffusion process at low frequency.